2020
DOI: 10.1186/s40643-020-00305-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of immobilized Lactobacillus pentosus cell fermentation for lactic acid production

Abstract: Parametric optimization is an effective way in fermentation process to improve product yield and productivity in order to save time, space and financial resources. In this study, Box-Behnken design was applied to optimize the conditions for lactic acid production by immobilized Lactobacillus pentosus ATCC 8041 cell fermentation. Two quadratic models and response surface methodology were performed to illustrate the effect of each parameters and their interactions on the lactic acid yield and glucose consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
(76 reference statements)
3
18
0
Order By: Relevance
“…It is noted that increasing the initial sugar concentration (45, 70, 88, and 117 g/L) in the fermentation broth led to a slight decrease in lactic acid yield (0.98, 0.95, 0.95, and 0.92 g/g, respectively) but a significant increase in lactic acid productivity (0.34, 0.49, 0.61, and 0.76 g/L/h, respectively) (Table 1). Similar trend was found in a previous study which reported that increasing the initial glucose concentration from 100 g/L to 120 g/L increased the fermentation productivity but decreased the lactic acid yield from 0.94 g/g to 0.92 g/g (Wang et al, 2020). Small amount of acetic acid (less than 1 g/L for all four groups) was produced during fermentation with the trend similar to lactic acid production-increasing initial sugar concentration increased acetic acid concentration (Figure 2d).…”
Section: Effect Of Initial Sugar Concentration On the Fermentation Of...supporting
confidence: 91%
See 1 more Smart Citation
“…It is noted that increasing the initial sugar concentration (45, 70, 88, and 117 g/L) in the fermentation broth led to a slight decrease in lactic acid yield (0.98, 0.95, 0.95, and 0.92 g/g, respectively) but a significant increase in lactic acid productivity (0.34, 0.49, 0.61, and 0.76 g/L/h, respectively) (Table 1). Similar trend was found in a previous study which reported that increasing the initial glucose concentration from 100 g/L to 120 g/L increased the fermentation productivity but decreased the lactic acid yield from 0.94 g/g to 0.92 g/g (Wang et al, 2020). Small amount of acetic acid (less than 1 g/L for all four groups) was produced during fermentation with the trend similar to lactic acid production-increasing initial sugar concentration increased acetic acid concentration (Figure 2d).…”
Section: Effect Of Initial Sugar Concentration On the Fermentation Of...supporting
confidence: 91%
“…This productivity was 4.1 times higher than that of fermentations conducted in shaking flasks (Table 1). The same optimal pH (6.0) result was also reported by a previous study applying L. pentosus ATCC 8041 strain to produce lactic acid (Wang et al, 2020). Increasing the pH to 7.0 led to a decrease in glucose and fructose utilization, especially fructose utilization (Figure 3b).…”
Section: Effect Of Controlling Ph On the Fermentation Of Food Waste H...supporting
confidence: 85%
“…The adjusted R 2 and predicted R 2 were 0.9864 and 0.9660, respectively, and the difference was less than 0.2, suggesting that the model value was highly accurate with a reasonable prediction [19]. The F ‐value of “lack of fit” was not significant, implying that the model was proper and reliable [16–20]. The adequate precision of 55.2309 was larger than 4, which indicated that this model was able to predict conditions of the biomass concentration in batch fermentation by L. pentosus ATCC 8041 cells with high precision [5].…”
Section: Resultsmentioning
confidence: 99%
“…Functional metabolite abundance differences were assessed using the KEGG Database and the heat map generated using HemI 2.0. 18,29 UV-visible and FT-IR spectrum analysis of the produced lactic acid…”
Section: Lc-ms Analysismentioning
confidence: 99%